MIKROENKAPSULASI MINYAK IKAN PORA-PORA (Mystacoleucus padangensis) MENGGUNAKAN METODE SPRAY DRYING UNTUK APLIKASI NUTRISI MAKANAN - Nirmala Efri Hasibuan; Thamrin Thamrin; Yugia Muis (JURNAL KIMIA MULAWARMAN, 2017)
The microencapsulated of Pora-Pora fish oil (Mystacoleucus padangensis) for food nutrition applications has been done. Production of fish oil using soxhletation extraction method with n-hexane for 6 hours. Manufactured of fish oil powder made by spray drying method using a coating material maltodextrin and gum arabic with a few variations. The characteristic of pora-pora fish oil has a yellow color, acid number 2.61 mg KOH/gr, free fatty acids (% oleic) 1.31 %, peroxide value 11.52 mek/kg, saponification value 89.76 mg KOH/gr and a water content of 0.3%. The composition of saturated fatty acid was 33.6 to 35%, and unsaturated fatty acids about 65 to 66.4%. Microencapsulated powder has a moisture content range from 4.8 to 7.3%, the yield ranged from 24.7 to 33.52%, and encapsulation efficiency maximum was 51%. The fatty acid composition has changed, the content of unsaturated fatty acids increased to 81, 1%. However, polyunsaturated fatty acids decreased.